2021
DOI: 10.3892/etm.2021.10504
|View full text |Cite
|
Sign up to set email alerts
|

A steroid‑induced osteonecrosis model established using an organ‑on‑a‑chip platform

Abstract: Bone microvascular endothelial cells (BMECs) constitute the central part of the femoral head's intramural microenvironment network and have an essential role in the development of steroid-induced osteonecrosis of the femoral head. Recently, the rapid development of microfluidic technology has led to innovations in the fields of chemistry, medicine and life sciences. It is now possible to use microfluidics organ-on-a-chip techniques to assess osteonecrosis. In the present study, BMECs were cultured on a microfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The BMECs were isolated following the methods described in the previous article [ 17 ]. The normal cancellous bone from the femoral head was processed into bone particles and washed with PBS thrice.…”
Section: Methodsmentioning
confidence: 99%
“…The BMECs were isolated following the methods described in the previous article [ 17 ]. The normal cancellous bone from the femoral head was processed into bone particles and washed with PBS thrice.…”
Section: Methodsmentioning
confidence: 99%
“…Bone microvessels are monolayer structures essential for bone formation and metabolism, and direct contact with ingredient in the blood. 98 In our former study, it could be found that glucocorticoid intervention could induce apoptosis of the BMECs and enhance eleven cytokines in the released extracellular vesicles ( Figure 5 ). 98 , 99 Among them, S100A8 (Fold change = 56.23) is an atypical inflammatory cytokine that is most markedly elevated, which could also promote the M1 polarization of macrophage and the chronic inflammatory processes by activating the TLR4/NF-κB signal pathway according to published article.…”
Section: Mechanism Underlying the Macrophage Polarization Imbalance I...mentioning
confidence: 85%
“… 98 In our former study, it could be found that glucocorticoid intervention could induce apoptosis of the BMECs and enhance eleven cytokines in the released extracellular vesicles ( Figure 5 ). 98 , 99 Among them, S100A8 (Fold change = 56.23) is an atypical inflammatory cytokine that is most markedly elevated, which could also promote the M1 polarization of macrophage and the chronic inflammatory processes by activating the TLR4/NF-κB signal pathway according to published article. 100 The glucocorticoid-induced injury of bone microvascular endothelial vessels and subsequently enhanced level of BMECs-derived cytokines may act as a prerequisite for the macrophage-induced chronic inflammation in GIONFH.…”
Section: Mechanism Underlying the Macrophage Polarization Imbalance I...mentioning
confidence: 85%
“…We also added HA to the multicomponent compositions to simulate the proportion of mineral substances in bone tissues. Although previous reports indicated that the two-component culture of HA and BMECs could enhance the cell growth (Li et al, 2021), the effects on cell growth and angiogenesis status in multi-component culture pattern still remains unclear. Our design of three parallel culture patterns was to make sure that each group must be cultivated under the same circumstance.…”
Section: Discussionmentioning
confidence: 96%